Gamifying Vocabulary Learning: The Development of Scratch-Based Interactive Media for Teaching Animal Names in Elementary Schools - Wardani Rahman, Naufalia; Korotul Aini, Sitti; Salym Muqaddam, Amiel; Wahyuli, Sabrina; Anjarani, Devie (UIBU, 2026)
Learning vocabulary from an early age is essential as it serves as a basis for students' language development. However, the use of monotonous teaching methods often leads to low student interest and limited understanding, particularly in learning animal names. This study aims to develop an interactive Scratch-based learning media that is valid and practical for use in the teaching and learning process. This study utilized the Research and Development (R&D) approach utilizing the ADDIE model, which includes analysis, stages of design, development, execution, and assessment. The participants were fifth-grade students of SDN Pademawu Timur 4, Pamekasan. Data were obtained from expert validation sheets and questionnaires completed by teachers and students, and then analyzed quantitatively to evaluate the validity and practicality of the developed media.. The results indicated that the developed media obtained validity scores of 0.83 from the media expert and 0.82 from the expert material, categorized as high validity. Furthermore, the practicality level reached 92% from teachers and 90% from students, categorized as very practical. Therefore, The use of Scratch-based learning media suggests that interactive and visual programming tools can improve elementary students’ engagement and motivation in learning English.